Editorial - Yuet, Fanny Kho Chee (Management Research Journal, 2021)
The Management Research Journal, Special Issue (2021), comprises 12 articles that present current issues in educational leadership and management in the volatility, uncertainty, complexity, and ambiguity (VUCA) world from Malaysia.  Eight articles that frame educational leadership are from Sultan Idris Education University, and an article on educational management from the Ministry of Education Malaysia as well as the Institute of Teacher Education is also respectively presented.  The selected eleven articles focus on leadership and only one article focuses on educational management.